The Influence Of Asset Growth And Capital Structure On Profitability In The Food And Beverage Sub-Sector Companies Listed On The Indonesian Stock Exchange For The 2020-2024 Period - Alya Fadiyah Dwi Putri; Chalid Imran Musa; Annisa Paramaswary Aslam (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2026)
This study aims to analyze the influence of asset growth and capital structure on profitability in food and beverage sub-sector companies listed on the Indonesia Stock Exchange for the 2020–2024 period. The research was motivated by the dynamic competition within the food and beverage industry, which demands companies to maintain efficient asset management and an optimal capital structure to sustain profitability. Using a quantitative approach with multiple linear regression analysis, data were collected from 17 companies that met the research criteria, resulting in 85 firm-year observations. The results of the t-test show that asset growth has a positive but not significant effect on profitability (ROA), while the Debt to Equity Ratio (DER) has a positive and significant effect. Furthermore, the F-test indicates that both variables simultaneously have a significant effect on profitability, implying that the model used is feasible to explain the relationship between independent and dependent variables. These findings suggest that efficient asset expansion combined with a balanced capital structure can enhance corporate profitability. The study supports financial theories such as the Trade-Off Theory and Pecking Order Theory, emphasizing the importance of balancing internal and external financing for sustainable financial performance. The research contributes empirically to understanding profitability determinants in Indonesia's manufacturing sector. It also provides practical implications for corporate managers to optimize asset growth strategies and debt management. However, the study is limited by its sample size and observation period, so future research is recommended to expand the sample scope and include other financial variables.